Rapid quantitative detection method for quartz gas-liquid inclusion
By crushing quartz sand and observing polarization microscopy, combined with pixel analysis of data processing servers, rapid quantitative detection of gas-liquid inclusions in quartz sand is achieved, solving the problems of inaccurate detection and low efficiency in traditional methods, and providing evaluation standards for high-purity quartz raw materials.
Patent Information
- Application Number
- CN202410506469.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-07-01
AI Technical Summary
The prior art is difficult to conduct quantitative detection of gas-liquid inclusions in quartz sand quickly and accurately, resulting in inaccurate screening and evaluation of quartz raw materials, and traditional methods take a long time and are inefficient.
The quartz sample was broken into 100-300μm particle-grade quartz sand, and the oil-immersed sheet was observed through a polarization microscope. The pixel proportion of quartz sand particles was calculated using a data processing server, and divided into permeable, semi-permeable and impermeable particles for quantitative analysis and grading.
Comprehensive and quantitative detection of gas-liquid inclusions in quartz sand is achieved, the reliability and scientificity of the test results are improved, artificial errors are reduced, and the screening and evaluation standards for high-purity quartz raw materials are provided.
Smart Images

Figure CN120232774A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of fluid inclusion detection, and specifically relates to a rapid quantitative detection method for quartz gas-liquid inclusions. Background Art
[0002] Quartz sand is a mineral product purified from raw materials such as quartz crystals, vein quartz, and granitic pegmatite, and is also an important industrial mineral raw material. Quartz sand, especially high-purity quartz sand, is widely used in industries such as electronic information, photovoltaics, optical communication, and electric light sources, and plays an important role in the strategic emerging industries of new materials and new energy.
[0003] Mineral inclusions are part of the material that was trapped in lattice defects or cavities of minerals during the crystallization and growth of minerals from diagenetic and ore-forming fluids (fluids containing gas and liquid or silicate melts), and are still sealed in the host minerals and have a phase boundary with the host minerals. At the same time, they are also one of the important forms of existence of quartz impurity elements. The fluid medium captured during the formation of fluid inclusions is a supersaturated solution, and when the temperature drops, daughter minerals will crystallize from the solution. Rock salt is the most common daughter mineral, and potassium salts and some silicate minerals also appear in this way. Therefore, fluid inclusions contain impurities such as Na, K, Cl, and Ca, which are the main sources of alkali metal impurities in quartz. Therefore, selecting quartz raw materials with few or no fluid inclusions is the key to preparing high-purity quartz.
[0004] At present, the monitoring and detection of gas-liquid inclusions in quartz sand in the industry are mainly carried out by trial-producing quartz products. For example, trial-producing glass tubes or single-crystal crucibles to observe whether there are bubbles, flocculents, etc. These methods are time-consuming, require large investments, and at the same time cause a large amount of waste of quartz sand, and have many disadvantages. In addition, the detection of quartz gas-liquid inclusions can also be carried out through traditional process mineralogy research. Traditional process mineralogy research involves slicing quartz stones or slicing quartz sand after boiling with glue. The requirements for thin sections and inclusion sections are extremely high. They cannot be too thick or too thin, as either too thick or too thin will affect the observation effect and require high skills from operators. The cut thin sections or inclusion sections are then observed for gas-liquid inclusions through a polarized light microscope. Professional personnel need to search for gas-liquid inclusions within the field of view. Each field of view is very small, and not every field of view contains gas-liquid inclusions. Professional personnel selectively provide some photos for others to observe, and there is no quantitative method for gas-liquid inclusions in a certain field of view, resulting in the inability to accurately quantify the gas-liquid inclusions in quartz samples. Therefore, for the detection of gas-liquid inclusions in quartz sand, the process of traditional process mineralogy research cannot meet the requirements. In China, there are few achievements in the application of machine quantitative calculation of fluid inclusion content. "Zhao Yi, et al. Automatic Identification and Index Calculation of Quartz Fluid Inclusions Based on Machine Vision [J]. Conservation and Utilization of Mineral Resources, 2022, 42(5): 28-34." discloses a method for calculating the content of fluid inclusions in quartz through the change in the brightness of quartz particles in microscopic photos. This method is greatly affected by artificial sampling and has the disadvantages of low efficiency and difficulty in popularization.
[0005] Therefore, there is an urgent need for a highly efficient, accurate and reliable detection method to meet the requirements of quantitative detection of quartz gas-liquid inclusions in the industry. Summary of the Invention
[0006] In view of this, the purpose of this application is to provide a rapid quantitative detection method for quartz gas-liquid inclusions. That is, after simply preparing a quartz sample into a quartz sand sample, the content of gas-liquid inclusions in the quartz sand is calculated by the pixel ratio of gas-liquid inclusions in the polarized light microscope image, providing a key index for the screening and evaluation of high-purity quartz raw materials.
[0007] To achieve the above purpose, this application provides the following technical solutions:
[0008] A rapid quantitative detection method for quartz gas-liquid inclusions, comprising:
[0009] (1) Crushing the quartz sample to make quartz sand with a particle size of 100-300 μm;
[0010] (2) Uniformly spreading the quartz sand on a glass slide equipped with a sample cell, ensuring that the quartz sand does not accumulate, dropping immersion oil onto the quartz sand to immerse it, and covering it with a coverslip to obtain an oil-immersed slide to be detected;
[0011] (3) Use a microscope to take all-round photos of the oil immersion slide, obtain the photos and store them.
[0012] (4) Transmit the stored photos to the data processing server. The data processing server extracts the pixels of the quartz sand by segmenting the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand. Classify the quartz sand into transparent particles, semi-transparent particles and non-transparent particles according to the pixel proportion, and calculate the quantity proportion of the transparent particles, semi-transparent particles and non-transparent particles.
[0013] (5) Classify the quartz samples according to the quantity proportion of the transparent particles and non-transparent particles in the quartz sand.
[0014] Further, in step (2), the size of the sample cell is 10 mm × 10 mm × 0.5 mm, and the sizes of the glass slide and the cover glass are 1.5 cm × 1.5 cm.
[0015] Further, in step (2), the immersion oil is at least one of glycerin, cedarwood oil and Leica immersion oil.
[0016] Further, in step (3), the number of photos obtained is 20 - 30.
[0017] Further, in step (4), the transparent particles are quartz sand particles with the pixel proportion of the gas-liquid inclusions in the quartz sand less than 0.3%; the semi-transparent particles are quartz sand particles with the pixel proportion of the gas-liquid inclusions in the quartz sand being 0.3% - 5%; the non-transparent particles are quartz sand particles with the pixel proportion of the gas-liquid inclusions in the quartz sand greater than 5%.
[0018] Further, in step (5), the specific method for classifying the quartz samples is as follows: Classify the quartz samples into four categories A, B, C, and D, where:
[0019] Category A: The proportion of the number of transparent particles in the quartz sand ≥ 70%, and the proportion of non-transparent particles in the quartz sand ≤ 5%;
[0020] Category B: 50% ≤ the proportion of the number of transparent particles in the quartz sand < 70%, 5% < the proportion of non-transparent particles in the quartz sand ≤ 10%; or the proportion of the number of transparent particles in the quartz sand ≤ 20%, and the proportion of non-transparent particles in the quartz sand ≤ 5%;
[0021] Category C: 20% ≤ the proportion of the number of transparent particles in the quartz sand < 50%, 10% < the proportion of non-transparent particles in the quartz sand ≤ 30%; or the proportion of the number of transparent particles in the quartz sand ≤ 20%, 5% < the proportion of non-transparent particles in the quartz sand ≤ 10%;
[0022] Category D: The proportion of transparent particles in quartz sand is ≤ 20%, and the proportion of opaque particles in quartz sand is > 10%; or the proportion of opaque particles in quartz sand is ≥ 30%.
[0023] Compared with the prior art, it has at least the following advantages:
[0024] (1) The rapid quantitative detection method of quartz gas-liquid inclusions provided by this application can quantitatively detect the overall situation of gas-liquid inclusions in quartz ore. The existing methods of observing gas-liquid inclusions after slicing or detecting gas-liquid inclusions in the microscopic area of quartz sand are all carried out on the local part of quartz and can only be qualitatively described to determine whether there are more or fewer gas-liquid inclusions; while the detection method provided by this application can comprehensively and quantitatively detect hundreds or thousands of particles, and the detection results are more reliable, more effective and more instructive.
[0025] (2) It is innovative to use the proportion of the number of transparent particles and opaque particles to quantitatively describe the content of quartz gas-liquid inclusions in this application. This method observes by preparing quartz into quartz sand instead of directly observing quartz blocks. The detection data is more comprehensive and accurate because the process of preparing quartz blocks into finer-grained quartz sand is a process of uniform mixing, and the results of quartz sand can better represent the overall situation of the quartz sample rather than the local situation. By classifying quartz into four categories of A, B, C, and D with excellent to poor ore quality for hierarchical utilization according to the proportion of the number of transparent particles and opaque particles in quartz sand, it has scientificity and comprehensiveness.
[0026] (3) In the rapid quantitative detection method of quartz gas-liquid inclusions provided by this application, it is completed by a data processing server with image recognition and calculation functions, reducing the errors caused by human intuitive judgment. Through the efficient calculation of the data processing server and the centralized processing and automatic storage of data, the reliability of the detection results of the content of quartz gas-liquid inclusions is improved. Description of the Drawings
[0027] Figure 1 It is the feedback result of the quartz sand particles of the first quartz sample extracted by the data processing server.
[0028] Figure 2 It is the feedback result of the quartz sand particles of the second quartz sample extracted by the data processing server.
[0029] Figure 3 It is the feedback result of the quartz sand particles of the third quartz sample extracted by the data processing server.
[0030] Figure 4 It is the feedback result of the quartz sand particles of the fourth quartz sample extracted by the data processing server. Detailed Embodiments
[0031] In order to make the objectives, technical solutions, and advantages of this application more clear and understandable, the following further elaborates on this application in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit this application.
[0032] Gas-liquid inclusions refer to gas or liquid impurities inside quartz particles, which have different light refraction properties from quartz itself. By adding a special reagent (immersion oil), the refraction differences between quartz sand particles are eliminated, and the refraction properties between quartz sand particles are the same as those of quartz itself. Due to different refraction properties (pixel proportion), the gas and liquid inside quartz sand particles appear black or dark, resulting in poor particle permeability. The more gas-liquid inclusions there are, the more black and dark parts there are, and the worse the permeability of quartz sand particles. If the dark part on a certain quartz sand particle is higher than a certain proportion, it is defined as an opaque particle, that is, a quartz sand particle with a very high gas-liquid inclusion content, while a transparent particle refers to a quartz sand particle with a very low gas-liquid inclusion content.
[0033] Based on this, the embodiments of this application provide a rapid quantitative detection method for quartz gas-liquid inclusions, including: crushing a quartz sample to make quartz sand with a particle size of 100-300 μm; evenly spreading the quartz sand on a glass slide equipped with a sample cell, ensuring that the quartz sand does not accumulate, dropping immersion oil on the quartz sand to immerse it, covering it with a cover glass to obtain an oil-immersed slide to be detected; using a microscope to take omnidirectional photos of the oil-immersed slide, obtaining and storing the photos; transmitting the stored photos to a data processing server, and the data processing server extracts the pixels of the quartz sand by segmenting the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand; classifying the quartz sand into transparent particles, semi-transparent particles, and opaque particles according to the pixel proportion, and calculating the quantity proportions of the transparent particles, semi-transparent particles, and opaque particles; and grading the quartz sample according to the quantity proportions of the transparent particles and opaque particles in the quartz sand.
[0034] In some embodiments, the size of the sample cell is 10 mm × 10 mm × 0.5 mm, and the sizes of the glass slide and the cover glass are 1.5 cm × 1.5 cm.
[0035] In some embodiments, the immersion oil is at least one of glycerol, cedarwood oil, and Leica immersion oil. The refractive index of air is 1.0, while the refractive indices of the glass slide and the cover glass are usually about 1.5. The refractive index of the immersion oil is also about 1.5. The purpose is to match the refractive indices of the glass slide and the cover glass to make them as close as possible, so as to avoid the influence on detection caused by different refractive indices of air and the glass slide.
[0036] In some embodiments, the number of photos taken of the oil immersion slide using a microscope is such that the quartz sand particles (300 - 500) on the glass slide can be captured in all directions. A photo count of 20 - 30 can meet this requirement, thus ensuring the accuracy of subsequent statistical analysis.
[0037] In some embodiments, the microscope is a polarizing microscope. A polarizing microscope is a type of microscope used to study so-called transparent and opaque anisotropic materials. Any substance with birefringence can be clearly distinguished under a polarizing microscope. Based on an ordinary optical microscope, a polarizing microscope changes ordinary light into polarized light for microscopic examination to identify whether a substance is singly refractive (isotropic) or birefringent (anisotropic).
[0038] In some embodiments, the permeable particles are quartz sand particles with a pixel ratio of quartz sand gas-liquid inclusions lower than 0.3%; the semi-permeable particles are quartz sand particles with a pixel ratio of quartz sand gas-liquid inclusions between 0.3% and 5%; the impermeable particles are quartz sand particles with a pixel ratio of quartz sand gas-liquid inclusions higher than 5%.
[0039] In some embodiments, the specific method for classifying quartz samples is as follows: The quartz samples are divided into four categories, A, B, C, and D, where:
[0040] Category A: The proportion of permeable particles in the quartz sand is ≥70%, and the proportion of impermeable particles in the quartz sand is ≤5%;
[0041] Category B: 50% ≤ the proportion of permeable particles in the quartz sand < 70%, 5% < the proportion of impermeable particles in the quartz sand ≤ 10%; or the proportion of permeable particles in the quartz sand ≤ 20%, and the proportion of impermeable particles in the quartz sand ≤ 5%;
[0042] Category C: 20% ≤ the proportion of permeable particles in the quartz sand < 50%, 10% < the proportion of impermeable particles in the quartz sand ≤ 30%; or the proportion of permeable particles in the quartz sand ≤ 20%, 5% < the proportion of impermeable particles in the quartz sand ≤ 10%;
[0043] Category D: The proportion of permeable particles in the quartz sand ≤ 20%, and the proportion of impermeable particles in the quartz sand > 10%; or the proportion of impermeable particles in the quartz sand ≥ 30%.
[0044] The technical solutions and effects of the present application will be described in detail below through more specific embodiments.
[0045] Take four quartz samples from different sources, named the first quartz sample, the second quartz sample, the third quartz sample, and the fourth quartz sample respectively.
[0046] Example 1
[0047] Take a No. 1 quartz sample, crush the quartz sample to obtain quartz sand with a particle size of 100 - 300 μm, evenly spread the quartz sand on a glass slide (1.5 cm × 1.5 cm) equipped with a 10 mm × 10 mm × 0.5 mm sample cell, ensure that the quartz sand does not accumulate, add 1 ml of glycerol (refractive index 1.47) to immerse the quartz sample particles, cover with a cover glass (1.5 cm × 1.5 cm) to obtain an oil-immersed slide to be detected; after placing the oil-immersed slide in the fixed position of a polarized light microscope, the oil-immersed slide automatically moves along the XY direction, and the polarized light microscope takes full-coverage microscope images of the prepared oil-immersed slide to obtain 20 images, transfer the 20 obtained images to a data processing server, and the data processing server segments and extracts the pixels of the quartz sand through the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand; classify the quartz sand into transparent particles, semi-transparent particles and non-transparent particles according to the pixel proportion, and calculate the quantity proportion of the transparent particles, semi-transparent particles and non-transparent particles; classify the quartz sample according to the quantity proportion of the transparent particles and non-transparent particles in the quartz sand.
[0048] Figure 1 It shows the feedback result of the quartz sand particles of the No. 1 quartz sample extracted by the data processing server. According to the calculation result of the data processing server, the proportion of transparent particles in the No. 1 quartz sample is 94%, and the proportion of non-transparent particles is 0.8%. It is determined that the No. 1 quartz sample is Class A quartz.
[0049] Example 2
[0050] Take a No. 2 quartz sample, crush the quartz sample to obtain quartz sand with a particle size of 100 - 300 μm, evenly spread the quartz sand on a glass slide (1.5 cm × 1.5 cm) equipped with a 10 mm × 10 mm × 0.5 mm sample cell, ensure that the quartz sand does not accumulate, add 1 ml of cedar oil (refractive index 1.51) to immerse the quartz sample particles, cover with a cover glass (1.5 cm × 1.5 cm) to obtain an oil-immersed slide to be detected; after placing the oil-immersed slide in the fixed position of a polarized light microscope, the oil-immersed slide automatically moves along the XY direction, and the polarized light microscope takes full-coverage microscope images of the prepared oil-immersed slide to obtain 25 images, transfer the 25 obtained images and the sample pre-treatment information to a data processing server, and the data processing server segments and extracts the pixels of the quartz sand through the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand; classify the quartz sand into transparent particles, semi-transparent particles and non-transparent particles according to the pixel proportion, and calculate the quantity proportion of the transparent particles, semi-transparent particles and non-transparent particles; classify the quartz sample according to the quantity proportion of the transparent particles and non-transparent particles in the quartz sand.
[0051] Figure 2It shows the feedback results of the quartz sand particles of the second quartz sample extracted by the data processing server. According to the calculation results of the data processing server, the proportion of permeable particles in the second quartz sample is 75%, and the proportion of impermeable particles is 7%. It is determined that the second quartz sample is Class B quartz.
[0052] Example 3
[0053] Take the third quartz sample, crush the quartz sample to obtain quartz sand with a particle size of 100 - 300 μm, evenly spread the quartz sand on a glass slide (1.5 cm × 1.5 cm) equipped with a 10 mm × 10 mm × 0.5 mm sample cell, ensure that the quartz sand does not accumulate, add 1 ml of Leica immersion oil (refractive index 1.51) to immerse the quartz sample particles, cover with a cover glass (1.5 cm × 1.5 cm) to obtain an oil-immersed slide to be detected; after placing the oil-immersed slide in the fixed position of the polarized light microscope, the oil-immersed slide automatically moves along the XY direction, and the polarized light microscope takes full-coverage microscope images of the prepared oil-immersed slide to obtain 28 images. Transmit the obtained 28 images and the sample pretreatment information to the data processing server. The data processing server extracts the pixels of the quartz sand by segmenting the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand; distinguish the quartz sand into permeable particles, semi-permeable particles and impermeable particles according to the pixel proportion, and calculate the quantity proportions of the permeable particles, semi-permeable particles and impermeable particles; classify the quartz sample according to the quantity proportions of the permeable particles and impermeable particles in the quartz sand.
[0054] Figure 3 It shows the feedback results of the quartz sand particles of the third quartz sample extracted by the data processing server. According to the calculation results of the data processing server, the proportion of permeable particles in the third quartz sample is 35%, and the proportion of impermeable particles is 28%. It is determined that the third quartz sample is Class C quartz.
[0055] Example 4
[0056] Take a No. 4 quartz sample, crush the quartz sample to obtain quartz sand with a particle size of 100 - 300 μm, evenly spread the quartz sand on a glass slide (1.5 cm × 1.5 cm) equipped with a 10 mm × 10 mm × 0.5 mm sample cell, ensure that the quartz sand does not accumulate, add 1 ml of glycerol (refractive index 1.47) to immerse the quartz sample particles, cover with a cover glass (1.5 cm × 1.5 cm) to obtain an oil-immersion slide to be detected; after placing the oil-immersion slide in the fixed position of a polarizing microscope, the oil-immersion slide automatically moves along the XY direction, and the polarizing microscope takes full-coverage microscope images of the prepared oil-immersion slide to obtain 30 images. Transmit the obtained 30 images and the sample pretreatment information to a data processing server. The data processing server segments and extracts the pixels of the quartz sand through the photos and calculates the pixel proportion of the gas-liquid inclusions in the quartz sand; classify the quartz sand into transparent particles, semi-transparent particles, and non-transparent particles according to the pixel proportion, and calculate the quantity proportions of the transparent particles, semi-transparent particles, and non-transparent particles; classify the quartz sample according to the quantity proportions of the transparent particles and non-transparent particles in the quartz sand.
[0057] Figure 4 It shows the feedback results of the quartz sand particles of the No. 4 quartz sample extracted by the data processing server. According to the calculation results of the data processing server, the proportion of transparent particles in the No. 4 quartz sample is 13%, and the proportion of non-transparent particles is 33%. It is determined that the No. 4 quartz sample is a Class D quartz.
[0058] In summary, the rapid quantitative detection method for quartz gas-liquid inclusions provided by the embodiments of the present application can effectively reflect the content of gas-liquid inclusions in quartz samples, successfully classify quartz samples of different qualities, and provides key indicators for the screening and evaluation of high-purity quartz raw materials.
[0059] The above has introduced the present application in detail. Specific examples are used in this article to elaborate on the principle and implementation manner of the present application. The description of the above embodiments is only used to help understand the present application and its core idea. It should be noted that for those of ordinary skill in the art in this technical field, without departing from the principle of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.
Claims
1. A rapid quantitative detection method for quartz gas-liquid inclusions, characterized in that: include: (1) crushing the quartz sample to produce quartz sand with a particle size of 100 to 300 μm; (2) Evenly spread quartz sand on a glass slide equipped with a sample groove, drip immersion oil into the quartz sand to immerse it, cover it with a cover glass, and obtain an oil-immersion slide to be tested; (3) Using a microscope to take pictures of the oil-immersed slide in all directions, obtain the pictures and store them; (4) transmitting the stored photos to a data processing server, wherein the data processing server segments and extracts the pixels of the quartz sand through the photos, and calculates the pixel ratio of the gas-liquid inclusions in the quartz sand; the quartz sand is divided into transparent particles, semi-transparent particles, and opaque particles according to the pixel ratio, and the number ratio of the transparent particles, the semi-transparent particles, and the opaque particles is calculated; (5) Quartz samples are graded according to the ratio of transparent particles to non-transparent particles in quartz sand.
2. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that: In step (2), the size of the sample tank is 10 mm×10 mm×0.5 mm, and the size of the slide glass and cover glass is 1.5 cm×1.5 cm.
3. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that: In step (2), the immersion oil is at least one of glycerin, cedar oil, and Leica immersion oil.
4. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that: In step (3), the microscope is a polarizing microscope.
5. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that: In step (3), the number of photos obtained is 20 to 30.
6. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that: In step (4), the transparent particles are quartz sand particles whose pixel ratio of quartz sand gas-liquid inclusions is less than 0.3%; the semi-permeable particles are quartz sand particles whose pixel ratio of quartz sand gas-liquid inclusions is 0.3% to 5%; and the opaque particles are quartz sand particles whose pixel ratio of quartz sand gas-liquid inclusions is greater than 5%.
7. The rapid quantitative detection method of quartz gas-liquid inclusions according to claim 1, characterized in that ,,In step (5), the specific method for grading the quartz samples is: categorizing the quartz samples into four categories: A, B, C, and D, where: Category A: The proportion of transparent particles in quartz sand is ≥70%, and the proportion of non-transparent particles in quartz sand is ≤5%; Category B: 50%≤permeable particles in quartz sand <70%, 5%<permeable particles in quartz sand ≤10%; or permeable particles in quartz sand ≤20%, permeable particles in quartz sand ≤5%; Category C: 20% ≤ the proportion of transparent particles in quartz sand < 50%, 10% < the proportion of non-transparent particles in quartz sand ≤ 30%; or the proportion of transparent particles in quartz sand ≤ 20%, 5% < the proportion of non-transparent particles in quartz sand ≤ 10%; Category D: The proportion of transparent particles in quartz sand is ≤20%, and the proportion of non-transparent particles in quartz sand is >10%; or the proportion of non-transparent particles in quartz sand is ≥30%.